Shrinkage of Spleen in Sickle Cell Thalassemia: A rare case report - Mone, Fabia Hannan; Roy, Kuntal; Halder, Soma; Sheefa, Maleeha (Jour Med Resh and Health Sci, 2021)
The most prevalent monogenic gene disorder caused by defective hemoglobin in the blood is thalassemia. Splenectomy (Total/partial) is considered to be the alternative treatment method based on hypersplenism or iron overload and is an inherited-autosomal-recessive disorder. In South Asia, the far east, the Middle East, and Eastern Mediterranean nations, it is more prevalent. Over 40,000 children are born with Thalassemia every year.